2015
DOI: 10.3389/fcimb.2015.00022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential genetic components involved in the deviant quorum-sensing signaling pathways of Burkholderia glumae through a functional genomics approach

Abstract: Burkholderia glumae is the chief causal agent for bacterial panicle blight of rice. The acyl-homoserine lactone (AHL)-mediated quorum-sensing (QS) system dependent on a pair of luxI and luxR homologs, tofI and tofR, is the primary cell-to-cell signaling mechanism determining the virulence of this bacterium. Production of toxoflavin, a major virulence factor of B. glumae, is known to be dependent on the tofI/tofR QS system. In our previous study, however, it was observed that B. glumae mutants defective in tofI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Chitinase encoding genes were previously found to be upregulated by c-di-GMP ( Zogaj et al, 2012 ). Furthermore, binding of c-di-GMP resulted in transcriptional regulation of anti-pathogen genes required for biofilm formation, adhesion, motility and synthesis of bacterial virulence factors ( Landini et al, 2010 ; Srivastava and Waters, 2012 ; Römling et al, 2013 ; An et al, 2014 ; Chen et al, 2015 ; Fazli et al, 2015 ; Steinberg and Kolodkin-Gal, 2015 ). Here, for the first time, to the best of our knowledge, the YajQ/c-di-GMP signaling system has been shown to underlie a mutualistic endophyte-host interaction of critical importance to its host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase encoding genes were previously found to be upregulated by c-di-GMP ( Zogaj et al, 2012 ). Furthermore, binding of c-di-GMP resulted in transcriptional regulation of anti-pathogen genes required for biofilm formation, adhesion, motility and synthesis of bacterial virulence factors ( Landini et al, 2010 ; Srivastava and Waters, 2012 ; Römling et al, 2013 ; An et al, 2014 ; Chen et al, 2015 ; Fazli et al, 2015 ; Steinberg and Kolodkin-Gal, 2015 ). Here, for the first time, to the best of our knowledge, the YajQ/c-di-GMP signaling system has been shown to underlie a mutualistic endophyte-host interaction of critical importance to its host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Some solos respond to an endogenous, non-AHL, ligand. The LuxR-type receptor PluR of Photorhabdus luminescens responds to α-pyrones, while the related organism Photorhabdus asymbiotica responds to dialkylresorcinols using the LuxR homolog PauR (Brachmann et al, 2013 ; Brameyer et al, 2014 , 2015 ; Brameyer and Heermann, 2015 ; Chen et al, 2015 ). The synthases for these molecules were determined to be PpyS and DarABC, respectively.…”
mentioning
confidence: 99%
“…A role in regulation of toxoflavin production has been demonstrated. Although QS‐defective ( tofI, tofR ) mutants of B. glumae do not produce toxoflavin in lysogenic broth, they do produce high levels of the toxin when grown to high density on solid media (Chen et al ., ). This indicates the existence of QS‐independent regulation of toxoflavin synthesis.…”
Section: Environmental Regulation Of Virulence Factorsmentioning
confidence: 97%
“…This indicates the existence of QS‐independent regulation of toxoflavin synthesis. A mutational analysis to identify potential components of this alternative pathway identified a role for the REC‐GGDEF domain protein DgcB, and the IclR family regulatory protein QsmR (Chen et al ., ). Mutation of these genes in a wild‐type QS‐proficient background showed that QsmR was required for toxoflavin production in both QS‐dependent and QS‐independent pathways, whereas DgcB only has a role in the QS‐independent pathway(s).…”
Section: Environmental Regulation Of Virulence Factorsmentioning
confidence: 97%